posted by Presley on .
these questions are:
ELIMINATION USING MULTIPLICATION:
2x + 5y = 3 2x + y = 3
-x + 3y =-7 5x + 3y = 2
I NEED HELP ASAP!!!!
If I were you, I would mutiply the bottom left clear through by 2 to get rid of the x's and leave the y's:
2+-2 opposites add up to zero
Do the same with the others on the right. -3 as a factor makes the y's go away so you have nothing but x's to do.
-6x+-3y=-9 and 5x+3y=2 Opposite 3's add up to zero.
-x=-7 which is the same as x=7
Introduce a factor that gives you only one variable letter to work with instead of two. Take -x times 2 to get -2x which adds up to zero when added to 2x. Boom, your x's are gone. Solve for y and use whatever y equals to find x back in the original equations. -3y+3y=0 for the other side, so you can knock out the y's. Figure out x. Go back and figure out y based upon x.
thnx i got the answers to that one but now im stuck on elimination using addition and subtraction.